2019
DOI: 10.1044/2018_jslhr-s-17-0468
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Question Intonation by Young Adult Cochlear Implant Users: Does Age at Implantation Matter?

Abstract: The purpose of this observational study was to investigate the properties of sentence-final prosody in yes/no questions produced by cochlear implant (CI) users in order to determine whether and how the age at CI implantation impacts CI users' production of question intonation later in life. Method: We acoustically analyzed recordings from 46 young adult CI users and 10 young adults with normal hearing who read yes/no questions. Of the 46 CI users, 20 had received their CI before the age of 4.0 years (early imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…The language development and memory skills were investigated in a limited number of studies with cochlear implanted adolescents using language-based skills. 38 39 40 41 In these studies, similar to our current study, it was found that adolescents who were implanted early had better performance in verbal working memory skills.…”
Section: Discussionsupporting
confidence: 88%
“…The language development and memory skills were investigated in a limited number of studies with cochlear implanted adolescents using language-based skills. 38 39 40 41 In these studies, similar to our current study, it was found that adolescents who were implanted early had better performance in verbal working memory skills.…”
Section: Discussionsupporting
confidence: 88%
“…Both early implantation age and longer hearing experience have been widely reported as beneficial for children with CIs' development on segmental and suprasegmental features, see e.g. studies on English, Cantonese and Spanish (Connor et al 2006;Dettman et al 2016;Lehnert-LeHouillier et al 2019;Sundarrajan et al 2019 ). The influence of age at implantation is likely related to a sensitive period in children's central auditory development, which has been suggested to occur between 3;6 and 7 years (Sharma, Dorman, and Kral 2005;Sharma, Nash, and Dorman 2009;Schorr et al 2005).…”
Section: Individual Differences Factors Affecting Speech Production In Children With Cismentioning
confidence: 99%
“…The decreased neural plasticity in late implanted children may adversely affect their neural organisation for audition and cause poor speech performance (Houston and Miyamoto 2010). The beneficial effect of longer device use experience, in turn, is related to language input and oral-aural communication practice (Sundarrajan et al 2019;Lehnert-LeHouillier et al 2019). For example, Sundarrajan et al (2019) demonstrated that children with CIs with longer device use had better consonant accuracy and a larger consonant inventory.…”
Section: Individual Differences Factors Affecting Speech Production In Children With Cismentioning
confidence: 99%
“…Along with some recent studies on speech production of users of CI (e.g. Holt & Fletcher, 2010; Lehnert-LeHouillier et al, 2019), in this article, the intonation contours were phonologically transcribed. We made our analysis in line with the AM theory (Ladd, 2008), instead of directly measuring acoustic cues such as F0, duration, and intensity.…”
Section: Introductionmentioning
confidence: 99%